2021
DOI: 10.2460/ajvr.82.7.566
|View full text |Cite
|
Sign up to set email alerts
|

Use of serum hyaluronic acid as a biomarker of endothelial glycocalyx degradation in dogs with septic peritonitis

Abstract: OBJECTIVE To describe daily changes in serum concentrations of hyaluronic acid (HA), a biomarker of endothelial glycocalyx degradation, in dogs with septic peritonitis and to determine whether relationships exist among serum concentrations of HA and biomarkers of inflammation and patient fluid status. ANIMALS 8 client-owned dogs. PROCEDURES Serum samples that had been collected for a previous study and stored at −80°C were used. Blood samples were collected at admission and daily thereafter during hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Increases were correlated with increased risk of mortality. Veterinary Species Shaw et al (2021) Septic peritonitis Serum HA Serum HA increased on day 2 or 3 of hospitalization. Interleukin-6 was a predictor of serum HA.…”
Section: Evidence For Eglx Involvement In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Increases were correlated with increased risk of mortality. Veterinary Species Shaw et al (2021) Septic peritonitis Serum HA Serum HA increased on day 2 or 3 of hospitalization. Interleukin-6 was a predictor of serum HA.…”
Section: Evidence For Eglx Involvement In Diseasementioning
confidence: 99%
“…Alterations in eGlx composition following an inflammatory insult is thought to be one of the earliest features of sepsis in humans ( Martin et al, 2016 , Steppan et al, 2011 ). Dogs with septic peritonitis have been shown to have increased hyaluronan concentrations on day 2 or 3 of hospitalisation compared to admission, these concentrations decreased during the recovery period ( Shaw et al, 2021 ). The same study identified relationships between serum interleukin (IL)− 6 and hyaluronan concentrations, suggesting an association between inflammation and eGlx degradation.…”
Section: Evidence For Eglx Involvement In Diseasementioning
confidence: 99%
“…This allows more fluid to leak from compromised blood vessels, exacerbates interstitial edema, and triggers intravascular coagulation [ 6 8 ]. In previous studies, conditions such as septic peritonitis and parvoviral infections have been associated with eGCX damage in dogs [ 9 , 10 ]. Human studies have shown that conditions such as hypertension, hypercholesterolemia, cardiovascular disease, chronic kidney disease, diabetes, atherosclerosis, hypervolemia (aggressive fluid resuscitation), and ischemia–reperfusion injury can also lead to eGCX degradation [ 11 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The challenges of direct visualisation has led to the development of less invasive, indirect methods of eGlx evaluation ( Nieuwdorp et al, 2008 , Constantinescu et al, 2011 ) such as measurement of circulating eGlx components measured in humans including syndecans, hyaluronan and chondroitin sulphate ( Padberg et al, 2014 ). Their use has been reported in naturally occurring diseases in dogs ( Lawrence-Mills et al, 2022 , Shaw et al, 2021 ). Other indirect methods of eGlx measurement include sidestream dark field imaging ( Martens et al, 2013 ), where eGlx depth is inferred.…”
mentioning
confidence: 99%